Giant residual dipolar 13C-1H couplings in high-spin Organoiron complexes: elucidation of their structures in solution by 13C NMR spectroscopy - Kruck, Matthias; Wadepohl, Hubert; Enders, Markus; Gade, Lutz H. (Chemistry - a European journal, 2013)
High-spin FeII-alkyl complexes with bis(pyridylimino)isoindolato ligands were synthesized and their paramagnetic 1H and 13C NMR spectra were analyzed comprehensively. The experimental 13C—1H coupling values are temperature (T−1)- as well as magnetic-field (B2)-dependent and deviate considerably from typical scalar 1JCH couplings constants. This deviation is attributed to residual dipolar couplings (RDCs), which arise from partial alignment of the complexes in the presence of a strong magnetic field. The analysis of the experimental RDCs allows an unambiguous assignment of all 13C NMR resonances and, additionally, a structural refinement of the conformation of the complexes in solution. Moreover the RDCs can be used for the analysis of the alignment tensor and hence the tensor of the anisotropy of the magnetic susceptibility.
Gesehen am 15.06.2021
Im Titel ist die Zahl "13" und "1" hochgestellt
Im Zusatz zum Titel ist die Zahl "13" hochgestellt